The Growing Threat of Boko Haram to Regional Security - Try Sjahputra, Hafidz Ridha; Tisso, Aru Rongchitim (Jurnal Studi Pemerintahan, 2021)
This Research will analyse and delves into one of the most notorious terrorist groups in today’s world Islamic State of West Africa commonly known as Boko Haram. Through this paper's medium, we will delve into one of the most brutal and heinous terrorist organisations that have created havoc which called as Boko Haram. Firstly, we will explore the historical origins of the Islamic state of western Africa formerly known as Boko Haram which is an affiliate of the Islamic State and also explore and understand the nature of the conflict in Africa. We will also delve into the links between the ISIS and Boko Haram and explore the modus operandi and strategies of the Islamic state in regrouping with the help of its affiliates in the new geographical territory after the fall of ISIS caliphate in Iraq and Syria in 2014. Additionally, we will provide counterterrorism strategies to prevent the rise Boko Haram in Nigeria and neighbouring countries.Keywords: Boko Haram, Insurgency, Nigeria, Regional Security